Characterization of blaNDM in two Escherichia coli ST1193 clinical isolates in the Gulf region - Clement Kin-Ming Tsui (21978321) (2024)
Introduction Escherichia coli ST1193 is an emerging high-risk clone associated with the production of plasmid-mediated CTX-type extended-spectrum β-lactamases. However, this clone has seldom been found to contain plasmids carrying carbapenemase genes. We report two epidemiologically unlinked multidrug-resistant (MDR) clinical isolates of E. coli ST1193 with plasmids harbouring NDM-type carbapenemase genes from the Gulf region. Methods The isolates were identified by MALDI-TOF MS and antibiotic susceptibility testing was performed using the VITEK 2/Phoenix system. A conjugation experiment was performed to assess the transferability of the resistance plasmids. Genomic DNA of both isolates was subject to Illumina sequencing; one isolate was also sequenced using Oxford Nanopore technology. Bioinformatics analyses were performed to detect antimicrobial resistance genes, and to annotate the genetic context of the NDM genes. Results and Conclusions Both isolates were resistant to carbapenems using phenotypic tests. Conjugation experiment confirmed that NDM-5-encoding plasmids of both strains could be transferred to the recipient cells. The completed NDM-5-encoding plasmid of E. coli isolate FQ71 was highly similar to several plasmids from ST410 isolates in the NCBI database. Genomic analysis revealed the presence of transposase genes and transposons in the flanking regions of the NDM genes in the plasmids. Since carbapenems constitute first-line agents for the treatment of serious infections caused by ESBL producers, E. coli ST1193 isolates co-producing ESBL and NDM-type carbapenemases represent a serious challenge for antimicrobial stewardship and infection control programmes. Other Information Published in: JAC-Antimicrobial Resistance License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jacamr/dlae166